A Y-chromosome portrait of the population of Jerba (Tunisia) to elucidate its complex demographic history - Manni, F.; Leonardi, P.; Patin, É; Berrebi, A.; Khodjet-Elkhil, Houssein; Skorecki, K.; Rosengarten, D.; Rouba, H.; Heyer, Evelyne; Fellous, M. (Bulletins et mémoires de la Société d’Anthropologie de Paris, 2005)
L’histoire démographique de l’île de Jerba est très ancienne en raison de sa position centrale dans le bassin de la mer Méditerranée, c’est la raison pour laquelle plusieurs populations se sont succédées sur l’île dont la population est, de nos jours, hétérogène (Arabes, Berbères, Noirs, Juifs). Afin d’étudier la variabilité du chromosome Y de la population de Jerba nous avons analysé 10 polymorphismes, SRY-2627 ; SRY-10831a ; SRY-4064 ; 92R7 ; Tat ; YAP ; M2 ; LLY22g ; M9 ; 12f2q sur un échantillon de 127 individus (Juifs N = 32 ; Berbères N = 46 ; Arabes N = 47). Nous avions aussi échantillonné la population noire de Jerba mais des ambiguïtés, lors du génotypage, nous ont forcé à exclure l’échantillon de l’article. Les résultats indiquent une très faible différenciation génétique entre les échantillons arabe et berbère qui peuvent être considérés, d’un point de vue génétique, comme une seule population. Inversement, les mesures de FST montrent que les distances entre l’échantillon juif et les autres groupes ethniques de l’île sont considérables. Ce résultat implique un faible niveau d’échange génétique entre les communautés qui habitent l’île, à la seule exception des Arabes et des Berbères. Comme l’isolement géographique est inexistant à Jerba, les différences des profils alléliques entre les trois groupes s’expliquent par une provenance géographique différente et une barrière culturelle relative concernant Arabes, Berbères et Juifs. La comparaison entre la composition haplotypique de Jerba et celle de 19 populations de référence, localisées autour du bassin de la mer Méditerranée, montre la provenance nord-africaine des Berbères et des Arabes de Jerba. De la même façon, l’échantillon juif vient d’une population mère localisée au Moyen-Orient.
Keywords: Biologie -- Djerba

Observations on Tenebrionicds (Col. Heteromera) of Djerba (Tunisia): ecology and biogeography - Marcuzzi, Giorgio (Mediterránea. Serie de Estudios Biológicos, 2005)
Ecological and biogeographical characteristics of 14 species of Tenebrionids (Coleoptera Heteromera) so far known for the Djerba Island (Tunisia, Gulf of Gabes) are illustrated for the first time. Basing on distribution we may recognize South-Western Mediterranean species; 3 centro-southern Mediterranean; 1 extended to the shores of Mediterranean Basin; 1 Western-Mediterranean element; 2 limited to South Mediterranean coast east of Morocco; 1 extended from Morocco (Atlantic coast) to Iran and Northern Arabic Peninsula, 1 extended from Algeria to Iran; 1 endemic of Djerba (Stenohelops berettai Marcuzzi), 1 widely distributed (Mediterranean s. lato). The distribution if often of relict type, due probably to its age. Basing on ecology there are 2 psammophilous species, 4 steppic, 3 rather euryoikous. Most Djeba Tenebrionids can be considered steppic (litoral or continental). Beside an endemic, 3 species show a distribution limited to centro-southern part of Mediterranean; the other are Western Mediterranean or widely distributed species (Scleron armatum and still more Tentyriagrossa and Zophosis punctata. The Tenebrionid coenosis –as well as insect coenoses as a whole– are heavily menaced by the continuously increasing anthropization, with human density, agriculture, grazing and tourism. The former determines a pumping of water from pits, with a possible salification of the water table, harmful to both invertebrates and plants. The excavation of clay for handicraft is another menace to environment, here included landscape. Grazing is bringing about a reduction and sometimes disappearance of coastal dunes, because of destruction of local vegetation (especially Gramineae). Measures of conservation characteristics of landscape invoked due to the great ecological and biogeographical interest of Tenebrionid coenoses living on Djerba since Miocene, and due to the systematic status of some species, still discussed, in this as in many steppic and desertic North African localities.
Keywords: Biologie -- Djerba